2011
DOI: 10.1167/iovs.10-5960
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Retinal Function and Flicker Light-Induced Retinal Vascular Response in Normotensive Patients with Diabetes without Retinopathy

Abstract: In patients with diabetes, neural and neurovascular dysfunctions both precede the onset of clinically detectable DR. To which extent these abnormalities are related to each other remains to be determined. (ClinicalTrials.gov number, NCT00839150.)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
98
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(107 citation statements)
references
References 33 publications
9
98
0
Order By: Relevance
“…31 Because retinal blood flow is coupled with neuronal activity, reduced flicker light induced vasodilatation might also reflect neurodegeneration. In a recent investigation by Lecleire-Collet et al, a linear association was found between flicker light induced retinal arterial vasodilatation and electroretinographic abnormalities, 16 indicating that a reduced neural activity in the retina might cause a decreased flicker response in DM. We did not find a significant difference in the vascular response to flicker light between the patients with or without neuropathy.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…31 Because retinal blood flow is coupled with neuronal activity, reduced flicker light induced vasodilatation might also reflect neurodegeneration. In a recent investigation by Lecleire-Collet et al, a linear association was found between flicker light induced retinal arterial vasodilatation and electroretinographic abnormalities, 16 indicating that a reduced neural activity in the retina might cause a decreased flicker response in DM. We did not find a significant difference in the vascular response to flicker light between the patients with or without neuropathy.…”
Section: Discussionmentioning
confidence: 91%
“…[13][14][15] In addition, the microvascular response to flicker light requires retinal neural integrity, and electroretinographic investigations confirmed an impaired flicker response caused by disturbed neurovascular coupling. 16 Beside these functional disturbances in retinal microvascular blood flow, morphological alterations in retinal angioarchitecture are a common feature in developing diabetic retinopathy. 17,18 In a recent study, an increase in retinal vascular caliber could be observed in association with peripheral diabetic neuropathy.…”
mentioning
confidence: 99%
“…This is possible in the pre-DR stage (14)(15)(16)(17). Some functional studies have suggested visual impairment in diabetic patients without apparent DR, but these studies did not exclude changes in integrity of the barrier function using a quantitative method (2,(18)(19)(20)(21)(22)(23)(24)(25). The occurrence of structural changes indicating vascular damage is also quite disputed in type 1 diabetic patients at a preclinical stage (23,26), possibly because the way patients are phenotyped may vary across studies.…”
mentioning
confidence: 99%
“…A link of such deficits with parvo-and magnocellular impairment is, however, missing. Besides the changes in achromatic contrast sensitivity (20,22), there are also studies showing changed psychophysical and physiologic changes in these patients without DR, related to color contrast sensitivity (24,25) and multifocal electroretinogram (mfERG) responses (21). It remains unclear whether these changes can be present independently of vascular damage (e.g., if they could reflect direct neural damage).…”
mentioning
confidence: 99%
“…The flicker response has also been demonstrated to correlate with altered retinal neural function detected by electroretinogram [111], and with changes in retinal vessel caliber [112].…”
Section: Ocular-based Biomarkersmentioning
confidence: 97%